2018
DOI: 10.1021/acs.energyfuels.8b01888
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism for Migration and Layer Growth of Biomass Ash on Ilmenite Used for Oxygen Carrier Aided Combustion

Abstract: Biomass is recognized as a CO2-neutral energy resource. However, biomass is a challenging fuel to combust because of its heterogeneity with regard to the content of inorganic constituents, volatiles, and moisture. Oxygen carrier aided combustion (OCAC) is a process advancement that provides enhanced combustion in existing circulating fluidized bed (CFB) units. The oxygen carrier has a central role in the OCAC concept through the oxygen transport it provides. The natural mineral ilmenite (FeTiO3) has been ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
60
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(87 citation statements)
references
References 32 publications
(94 reference statements)
8
60
0
Order By: Relevance
“…In comparison to real ash interaction, phosphorus from bio ash has also been observed to accumulate on the surface of the ilmenite particles used in large scale experiments. 44 …”
Section: Resultsmentioning
confidence: 99%
“…In comparison to real ash interaction, phosphorus from bio ash has also been observed to accumulate on the surface of the ilmenite particles used in large scale experiments. 44 …”
Section: Resultsmentioning
confidence: 99%
“…Together with TiO 2 (rutile) it builts up KTi 8 O 16 . On the contrary, introduced calcium formed a two-layer structure around the Fe-rich outer layer with increasing operation time building up CaTiO 3 . During further experiments, Corcoran et al examined the mechanical development of sand and rock ilmenite over 15 days of OCAC operation.…”
Section: Theorymentioning
confidence: 99%
“…Nevertheless, the reactivity compared to other, e.g., Ni-based oxygen carrier is quite low, , while the reactivity with syngas is higher as for methane . The increasing porosity of the ilmenite particles during the activation process results in reduced mechanical stability and increased attrition risk in the FBC . However, ilmenite shows good fluidizability and stability in long-term tests …”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…Experimetal observations suggest that c) is the most encountered mode of ash-OC interaction. [184,203] For example, Corcoran et al [183] reported the migration of potassium and calcium from the ash layer into the ilmenite particle, forming KTi 8 O 16.5 and CaTiO 3 , respectively. At the same time, a calcium layer mixed with other ash components (e.g., Si and P) gradually developed over the surface of the ilmenite particles.…”
Section: Interaction Between Ocs and Ashmentioning
confidence: 99%